REPRESENTASI NILAI MORAL PADA FILM “AGAK LAEN” KARYA BENEDION RAJAGUKGUK (KAJIAN SOSIOLOGI SASTRA) - Vahlevi, Muhammad Reza; Puspitasari, Indah (ASMARALOKA: Jurnal Bidang Pendidikan, Linguistik, dan Sastra Indonesia, 2024)
This research aims to study and find representations of moral values ​​contained in the film "Agak Laen" by Benedion Rajagukguk. The subject of this research is the film "Agak Laen" which is analyzed using a literary sociology approach. This research was conducted to describe and analyze the moral values ​​depicted and implicitly contained in the film. This research uses a qualitative descriptive method, combining primary data obtained from the film "Agak Laen". Meanwhile, the secondary data used in this research was obtained from literature studies that have credibility. The data analysis technique that has been collected is carried out systematically using descriptive analysis techniques. The results of this research show that the film "Agak Laen" shows important moral values ​​to be imitated, while also offering entertainment in the form of fresh comedy that is in harmony with everyday life. The film also shows that moral values ​​are important, such as emphasizing the importance of honesty and support from loved ones in facing life's challenges.